Chlorite-rich clay associations in interbedded tuffs and mudstones: diagenetic implications - Scasso, Roberto Adrian; Capelli, Ignacio Andrés; Cravero, Maria Fernanda; Kietzmann, Diego Alejandro
The Upper Jurassic of two basins in southern South America and the Antarctic Peninsula is characterized by blackshale/mudstone-dominated marine successions with interbedded tuff beds milimetric to decimetric thick. Anoxicenvironment precluded bioturbation and sediment mixing, and favoured organic matter preservation (TOC 2-8%).Some of these successions may form unconventional oil reserves, such as the VacaMuerta Formation, and thereforethe study of clay mineralsis critical for the fracking process. As the clay mineral association developed ontuffs is totally diagenetic it may be regarded as a good tracer for the diagenetic grade. It is also remarkably differentfrom the clay mineral association in the background sediments.Most tuff beds in our case studies (the Ameghino Formation in the Larsen Basin, northeastern Antarctic Peninsulaand the VacaMuerta Formation in the Neuquén Basin, western Argentina) are massively replaced by carbonate,chlorite andillite-smectite interlayers (I/S). In the localities selected for this study both units underwent deep burialin the context of high geothermal gradient basins. Chlorite is more abundant than I/S in the tuffs and the oppositeis true for the background shales and mudstones.XRD studies (bulk rock and fraction <2 microns) show similar composition for clays in carbonatized tuffs (earlydiagenetic carbonatic concretions developed on tuffs) and argilitized tuffs (white/yellow, soft, plastically deformedthin beds). The main clay mineral in the tuffs of the VacaMuerta Fm is Fe-rich chlorite, with variable contributionof interstratified illite-smectite layers (I/S). The I/S have more smectite layers in the tuffs, that are characterized asR1 I/S, in contrast with the R3 I/S in the mudstones. To Max (498-528 °C) from Rock-Eval Pyrolysis indicate therocks are overmature and were submitted to temperatures about 150 °C (e.g. Peters, 1986).The tuffs and carbonatized tuffs in the Ameghino Formation also show abundant Fe-rich chlorite, with variablecontribution of I/S classified as R1 ...